2003
DOI: 10.1046/j.1442-2034.2003.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute generalized peritonitis in adult African patients: Assessment of severity using APACHE II score

Abstract: Background:  Generalized surgical acute abdomen is a significant cause of morbidity and mortality in the Nigerian environment. Severity assessment is useful in order to prioritize treatment and reduce morbidity and mortality. High severity scores are often faced with high morbidity and mortality; these patients, often require more intensive treatment than those with low severity scores. The purpose of this study was to assess the severity of generalized surgical acute abdomen in adult patients using the Acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 31 publications
9
12
0
Order By: Relevance
“…In this series, children younger than 10 years and young adults between the ages of 11 and 20 years accounted for over half of the cases. This finding is similar to that reported by Badoe 6 in Ghana, Adesunkanmi et al 7 . in Nigeria and studies from India 8 and Pakistan, 9 where the majority of the patients were below 40 years of age, but differs from studies from the West, where elderly and middle‐aged patients with gastroduodenal perforations and inflammatory conditions of the colon constitute a significant number of cases of perforation peritonitis 10 .…”
Section: Discussionsupporting
confidence: 90%
“…In this series, children younger than 10 years and young adults between the ages of 11 and 20 years accounted for over half of the cases. This finding is similar to that reported by Badoe 6 in Ghana, Adesunkanmi et al 7 . in Nigeria and studies from India 8 and Pakistan, 9 where the majority of the patients were below 40 years of age, but differs from studies from the West, where elderly and middle‐aged patients with gastroduodenal perforations and inflammatory conditions of the colon constitute a significant number of cases of perforation peritonitis 10 .…”
Section: Discussionsupporting
confidence: 90%
“…Various studies reported that peritonitis is more common in 2 nd and 3 rd decade of life due to increased incidence of acid peptic disease and its complication in this age group. [6,7,8] Male preponderance is comparable to many other studies as smoking, alcoholism, stress and dietary factors more prevalent in male sex. [9,10] Most common cause of surgical peritonitis was gastro duodenal perforation which is usually found in 1 st part of duodenum and around pylorus of stomach which is comparable with other studies.…”
Section: Observationsupporting
confidence: 60%
“…16,17 Although such a system for the evaluation of EVD would require validation before it could be used, it may be possible to develop a system similar to APACHE to predict the risk of death with the use of clinical data that are available on presentation. Other measures that were found to differ significantly between patients with fatal EVD and those with nonfatal EVD are shown in Table S11 in the Supplementary Appendix.…”
Section: Resultsmentioning
confidence: 99%